PENERAPAN KASUS ALGORITMA ASCENT HILL CLIMBING DALAM PERMAINAN PUZZLE 8 - Yosdarso Afero (STEKOM PRESS, 2021)
Puzzle game is a game that shifts numbers from a box consisting of nine boxes. Eight boxes must have values arranged in numerical order starting from numbers 1 to 8. Puzzle games can produce the correct sequence according to the initial state provided that they follow the rules established rules. Completion of this game using a heuristic method, using the Ascent hill Climbing algorithm. The working process of the Ascent hill Climbing method is a process of looking for several possible solutions in order to get the optimal value for solving the problem by arranging the values from the position of the smallest value to the position of the largest value. The problem that is often experienced in this case is a lack of user knowledge in the concept of puzzle game rules so that search results are difficult to find,with this method it can make it easier to solve puzzle game cases by following the game rules and done systematically so that Goals are quickly found. The Goal results obtained are in the form of steps in the process of finding a solution and calculating the time required in the search to find a solution.